Thermal transfer printing artificial stone plate as well as preparation method and application thereof
By combining corundum powder with a specific mesh number and quartz powder, combined with specific raw materials and six-sided pressurized heating transfer and multi-stage insulation process, the problems of artificial stone slabs are solved, and high-definition, depth and stable thermal transfer effects are achieved.
Patent Information
- Application Number
- CN202411919525.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The existing artificial stone slabs are prone to deformation, cracking, transfer blur, red edges and insufficient penetration depth of thermal transfer ink during thermal transfer.
A process of gradually cooling through hexagonal powder and multi-stage insulation is used to combine unsaturated resins, epoxy resins, peroxide curing agents, and γ-methacryloyloxypropyltrimethoxysilane coupling agents.
It achieves the effect of straightening, clear patterns, high penetration depth of transfer layer, and difficult to crack and deform through processing and cutting.
Smart Images

Figure BDA0005207611450000091 
Figure BDA0005207611450000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of artificial stone, and in particular relates to a thermal transfer artificial stone plate and a preparation method and application thereof. Background Art
[0002] Artificial quartz stone is made of quartz sand powder as the main filler, resin as the adhesive, vacuum high-frequency vibration pressing, and then heated to solidify and polish to obtain a new type of artificial stone. Although there are patterned plates imitating natural marble at home and abroad, the color is simple, there is no level, the pattern texture is rough and unnatural, let alone high imitation of natural marble texture. At the same time, due to the complex process, the production efficiency of patterned artificial quartz stone plates is low and the defect rate is high.
[0003] As people's quality of life improves, their requirements for home decoration are getting higher and higher, especially the demand for personalized customized decoration is becoming more and more common. Thermal transfer is an emerging printing process, which refers to the printing technology of first printing the pre-designed pattern on the thermal transfer paper through a high-precision digital inkjet machine, and then transferring the decorative pattern on the transfer paper to the surface of the decorated substrate by heating at 150-210℃. At present, the thermal transfer process has been widely used in plastics, cosmetics, toys, electrical appliances, building materials, gifts, food packaging, stationery and other industries, but its application on quartz is still in its initial stage, and there are many problems. For example, due to the high temperature of artificial stone thermal transfer, reaching 180-210℃, the board is cooled after the thermal transfer is completed, and the internal stress in the board is not completely released, the artificial stone board is prone to deformation, and the later product processing and cutting of the edge strips are prone to deformation or cracking after installation; and the artificial stone board is also prone to transfer blur, red edges, and insufficient penetration depth of thermal transfer ink.
[0004] Therefore, it is of great significance to provide an artificial stone plate which is flat, has a clear pattern, has a high penetration depth of the transfer layer, and is not easy to crack and deform during processing and cutting. Summary of the invention
[0005] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art and at least provide a beneficial choice. Specifically, the present invention provides an artificial stone plate which is flat, has a clear pattern, has a high penetration depth of the transfer layer, and is not easy to crack and deform during processing and cutting.
[0006] The invention concept of the present invention: the artificial stone plate of the present invention comprises resin, corundum powder, quartz powder, filler, curing agent, coupling agent; the particle size of the corundum powder is 70-450 mesh; the particle size of the quartz powder is 500-950 mesh. The combination of corundum powder and quartz powder of specific mesh number of the present invention makes the gap between the resin and the powder particles smaller, the transfer effect of the plate surface after transfer is clearer, the transfer depth is better, and the plate surface is flat and not easy to deform.
[0007] Therefore, a first aspect of the present invention provides a heat-transfer artificial stone board.
[0008] Specifically, the thermal transfer artificial stone plate includes resin, corundum powder, quartz powder, filler, curing agent, and coupling agent;
[0009] The particle size of the corundum powder is 70-450 mesh; the particle size of the quartz powder is 500-950 mesh.
[0010] Preferably, the particle size of the corundum powder is 150-400 mesh; the particle size of the quartz powder is 550-850 mesh.
[0011] Preferably, the resin includes at least one of an unsaturated resin and an epoxy resin.
[0012] Preferably, the curing agent includes at least one of tert-butyl peroxide 2-ethylhexanoate, methyl ethyl ketone peroxide, tert-butyl perbenzoate, ethylenediamine, and diethylenetriamine.
[0013] Preferably, the coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
[0014] Preferably, the filler comprises bentonite.
[0015] Preferably, in parts by weight, the artificial stone plate comprises 11-24 parts of resin, 36-70 parts of corundum powder, 20-42 parts of quartz powder, 1.8-8.5 parts of filler, 0.1-1.3 parts of curing agent, and 0.1-1.6 parts of coupling agent.
[0016] Further preferably, the artificial stone plate comprises, by weight, 12-22 parts of resin, 40-65 parts of corundum powder, 22-38 parts of quartz powder, 2-8 parts of filler, 0.15-1.0 parts of curing agent, and 0.2-1.2 parts of coupling agent.
[0017] Preferably, the artificial stone board further includes at least one of a heat stabilizer, a color paste and a color powder.
[0018] Preferably, the artificial stone board also includes a heat stabilizer, a color paste and a color powder; and in terms of weight, the artificial stone board includes 11-24 parts of resin, 36-70 parts of corundum powder, 20-42 parts of quartz powder, 1.8-8.5 parts of filler, 0.1-1.3 parts of curing agent, 0.1-1.6 parts of coupling agent, 0.3-2.2 parts of heat stabilizer, greater than 0 parts and less than or equal to 0.60 parts of color powder, and greater than 0 parts and less than or equal to 2.4 parts of color paste.
[0019] Further preferably, the artificial stone board also includes a heat stabilizer, a color paste and a color powder; and in parts by weight, the artificial stone board includes 12-22 parts of resin, 40-65 parts of corundum powder, 22-38 parts of quartz powder, 2-8 parts of filler, 0.15-1.0 parts of curing agent, 0.2-1.2 parts of coupling agent, 0.3-2.0 parts of heat stabilizer, greater than 0 parts and less than or equal to 0.55 parts of color powder, and greater than 0 parts and less than or equal to 2.2 parts of color paste.
[0020] Preferably, the thermal stabilizer includes at least one of lithium stearate and zinc stearate.
[0021] Preferably, the color powder includes at least one of titanium dioxide, iron oxide red powder, iron oxide yellow powder, iron oxide black powder, phthalocyanine blue powder and carbon black powder.
[0022] Preferably, the color paste includes at least one of titanium white paste, iron yellow paste, carbon black paste, scarlet paste and phthalocyanine blue paste.
[0023] Preferably, the particle size of the bentonite is 900-3300 mesh; further preferably, the particle size of the bentonite is 1000-3000 mesh.
[0024] The second aspect of the present invention provides a method for preparing the thermal transfer artificial stone plate described in the first aspect of the present invention.
[0025] Specifically, the method for preparing the thermal transfer artificial stone plate comprises the following steps:
[0026] (1) mixing, shaping and curing the raw material components to obtain the semi-finished artificial stone slab;
[0027] (2) preheating, thermally transferring, and multi-stage cooling the semi-finished artificial stone slab obtained in step (1) to obtain the artificial stone slab;
[0028] The thermal transfer is to heat the artificial stone slab semi-finished product on six sides;
[0029] The multi-stage cooling includes four-stage cooling.
[0030] Preferably, in step (1), the forming is compression forming; further preferably, the forming is compression forming under vacuum conditions.
[0031] Preferably, in step (1), the curing temperature is 140-160°C, and the curing time is 110-130 min; further preferably, the curing temperature is 145-155°C, and the curing time is 115-125 min; further preferably, the curing temperature is 150°C, and the curing time is 120 min.
[0032] Preferably, in step (1), the process of thickness determination and polishing is also included after curing.
[0033] Preferably, in step (2), the preheating temperature is 110-150°C, and the preheating time is 1.8-11 min; further preferably, the preheating temperature is 120-140°C, and the preheating time is 2-10 min.
[0034] Preferably, in step (2), after the preheating, transfer paper is placed on the semi-finished artificial stone slab, covered with a high-temperature heat-conductive cloth, and sent to a transfer machine for thermal transfer.
[0035] Preferably, in step (2), the temperature of the thermal transfer is 180-220° C., and the time of the thermal transfer is 25-35 min; further preferably, the temperature of the thermal transfer is 190-210° C., and the time of the thermal transfer is 27-33 min.
[0036] Specifically, in step (2), the heating method of the thermal transfer is six-sided plywood heating, that is, the six sides of the semi-finished artificial stone slab are clamped in the six-sided plywood for heating, and heat conduction is achieved through the heat-conducting oil pipes pre-buried in the steel plates of the six-sided plywood.
[0037] Preferably, in step (2), the four-stage cooling is sequentially: keeping warm at 210-155°C for 25-35 min, keeping warm at 150-125°C for 25-35 min, keeping warm at 120-85°C for 55-65 min, and keeping warm at 80-40°C for 55-65 min.
[0038] Further preferably, in step (2), the four-stage cooling is sequentially keeping warm at 210-160°C for 25-35 min, keeping warm at 150-130°C for 25-35 min, keeping warm at 120-90°C for 55-65 min, and keeping warm at 80-50°C for 55-65 min.
[0039] Specifically, the six-sided pressurized heating transfer method of the present invention makes the temperature more uniform during thermal transfer, the transfer depth deeper, and the board surface more three-dimensional. The multi-stage insulation and gradual cooling method can prevent the internal stress generated by the board from being completely released due to excessive cooling, thereby avoiding deformation of the artificial stone board and cracking during later cutting.
[0040] The third aspect of the present invention provides an application of the artificial stone board described in the first aspect of the present invention in the field of construction.
[0041] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0042] (1) The combination of corundum powder and quartz powder of a specific mesh size in the present invention makes the gap between the resin and the powder particles smaller, the transfer effect of the plate surface after transfer is clearer, the transfer depth is better, and the plate surface is flat and not easy to deform.
[0043] (2) The six-sided pressurized heating transfer method of the present invention combined with the multi-stage insulation and gradual cooling method can make the temperature more uniform during transfer, the transfer depth deeper, and the three-dimensional effect of the board stronger; and it can avoid the internal stress generated by the board due to too rapid cooling not being completely released, thereby avoiding the deformation of the artificial stone board and cracking during later cutting.
[0044] (3) The patterns of natural stones are transferred to the polished semi-finished artificial stone products through a thermal transfer machine and transfer ink. No pre-spraying coating is required, and the transfer can be directly performed on the artificial stone slabs. The imitation of natural stone and wood grain is realistic, which makes it have broad application prospects in the decorative materials industry such as quartz stone, and truly promotes the quartz stone industry into the digital industrial era and intelligent industrial industry. Compared with ceramic tiles and rock slabs, it is more energy-saving, environmentally friendly and personalized, promoting the digital transformation of traditional quartz stone production and decoration technology.
[0045] (4) The patterns and textures of thermal transfer artificial stone panels are realistic, the hardness is high, the thickness can be made thin for easy processing, and it can remain straight and not deformed. At the same time, its patterns are clearer and richer than those of ordinary artificial stones, and its beauty and performance are more outstanding. The product is of high grade and can be easily applied to large-area wall panels, with broad market application prospects. DETAILED DESCRIPTION
[0046] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be noted that the following embodiments do not limit the protection scope of the present invention.
[0047] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0048] Example 1
[0049] A thermal transfer artificial stone plate comprises, by weight, 16.5 parts of vinyl unsaturated resin, 56.2 parts of 325-mesh corundum powder, 30 parts of 600-mesh quartz powder, 0.20 parts of tert-butyl peroxybenzoate, 0.22 parts of γ-methacryloxypropyltrimethoxysilane, 3.5 parts of 1000-mesh bentonite powder, 0.5 parts of lithium stearate heat stabilizer, 0.2 parts of composite color powder A (the mass ratio of titanium dioxide, iron red powder, iron yellow powder and iron black powder is 5:1:2:3) and 1.2 parts of composite color paste B (the mass ratio of titanium white paste, iron yellow paste, carbon black paste and scarlet paste is 8:2:2:1).
[0050] A method for preparing a thermal transfer artificial stone plate comprises the following steps:
[0051] (1) Stirring: Add vinyl unsaturated resin, tert-butyl peroxybenzoate curing agent, γ-methacryloxypropyl trimethoxysilane coupling agent, composite color paste, and heat stabilizer into a resin stirring barrel and stir evenly, then pour into a stirrer containing pre-mixed corundum powder, quartz powder, and bentonite powder, rotate forward at a low frequency of 10 Hz for 2 minutes, reverse at a low frequency of 10 Hz for 2 minutes, rotate forward at a high frequency of 50 Hz for 3 minutes, reverse at a high frequency of 50 Hz for 3 minutes, and stir and mix for 10 minutes to obtain a mixture;
[0052] (2) Powder spraying: pour the mixed material obtained in step (1) into the mold pad, flatten it, spray the composite color powder, and slightly stir the material layer to obtain a pre-pressed material;
[0053] (3) Vacuum pressing: The mold pad is fed into the press with the pre-pressed material sprayed with powder in step (2), and vacuumed. The material is vibrated at high frequencies in 8 frequency bands: 8 Hz for 20 seconds, 15 Hz for 20 seconds, 20 Hz for 40 seconds, 30 Hz for 30 seconds, 35 Hz for 30 seconds, 40 Hz for 30 seconds, 45 Hz for 60 seconds, and 50 Hz for 30 seconds. The phased and gradual vibration can effectively overcome the vibration problem caused by the excessive speed and haste of the traditional vibration machine.
[0054] (4) Curing and shaping: The plate pressed in step (3) is sent to a curing furnace, cured at 145° C. for 120 minutes, and then laid flat for shaping for 24 hours to obtain a embryonic plate;
[0055] (5) Thickness determination and polishing: The embryo plate obtained in step (4) is sent to a polishing machine for thickness determination, and then fine polishing is performed using grinding blocks of 26 mesh, 60 mesh, 100 mesh, 300 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1800 mesh, 3000 mesh, and 6000 mesh to obtain a semi-finished artificial stone plate of thermal transfer;
[0056] (6) Lay the semi-finished artificial stone plate obtained in step (5) flat, clean it and keep the surface flat, place the plate on the heat-insulating support plate via the conveyor line with a suction cup, and preheat it to a specified temperature of 130°C; then place the transfer paper printed with a high-definition stone pattern, cover it with a high-temperature heat-conducting cloth, and send it to the transfer machine. The heating method of thermal transfer is a six-sided plywood plate type. Heat conduction is achieved through a heat-conducting oil pipe pre-buried in the steel plate. The six-sided plywood oil tank is set to a heat transfer temperature of 210°C. When all six plywoods are in contact with the six sides of the artificial stone plate, the heating transfer time is maintained for 30 minutes, so that the pattern on the drawing is thermally sublimated, and the color is transferred and fused to the semi-finished artificial stone plate to obtain a plate after thermal transfer;
[0057] (7) The plate after thermal transfer in step (6) is transported from the transfer machine to a clamping plate type insulation furnace for four-stage cooling, wherein the four-stage cooling is firstly kept at 180°C for 30 minutes, then kept at 140°C for 30 minutes, kept at 110°C for 60 minutes, and kept at 70°C for 60 minutes; after the temperature is reduced to 40°C, it is sent to the wire rack and cooled to room temperature, and then a robot is used to separate the cooled artificial stone plate from the support plate to obtain the thermally transferred artificial stone plate.
[0058] Example 2
[0059] A heat transfer artificial stone plate comprises, by weight, 17 parts of vinyl unsaturated resin, 56.0 parts of 325-mesh corundum powder, 29.5 parts of 600-mesh quartz powder, 0.20 parts of tert-butyl peroxybenzoate, 0.23 parts of γ-methacryloxypropyltrimethoxysilane, 3.2 parts of 1000-mesh bentonite powder, 0.5 parts of lithium stearate heat stabilizer, 0.18 parts of composite color powder A (the mass ratio of titanium dioxide, iron red powder, iron yellow powder and iron black powder is 5:1:2:2) and 1.3 parts of composite color paste B (the mass ratio of titanium white paste, iron yellow paste, carbon black paste and scarlet paste is 8:2:1:2).
[0060] A method for preparing a thermal transfer artificial stone plate comprises the following steps:
[0061] (1) Stirring: Add vinyl unsaturated resin, tert-butyl peroxybenzoate curing agent, γ-methacryloxypropyl trimethoxysilane coupling agent, composite color paste, and heat stabilizer into a resin stirring barrel and stir evenly, then pour into a stirrer containing pre-mixed corundum powder, quartz powder, and bentonite powder, rotate forward at a low frequency of 10 Hz for 2 minutes, reverse at a low frequency of 10 Hz for 2 minutes, rotate forward at a high frequency of 50 Hz for 3 minutes, reverse at a high frequency of 50 Hz for 3 minutes, and stir and mix for 10 minutes to obtain a mixture;
[0062] (2) Powder spraying: pour the mixed material obtained in step (1) into the mold pad, flatten it, spray the composite color powder, and slightly stir the material layer to obtain a pre-pressed material;
[0063] (3) Vacuum pressing: The mold pad is fed into the press with the pre-pressed material sprayed with powder in step (2), and vacuumed. The material is vibrated at high frequencies in 8 frequency bands: 8 Hz for 20 seconds, 15 Hz for 20 seconds, 20 Hz for 40 seconds, 30 Hz for 30 seconds, 35 Hz for 30 seconds, 40 Hz for 30 seconds, 45 Hz for 60 seconds, and 50 Hz for 30 seconds. The phased and gradual vibration can effectively overcome the vibration problem caused by the excessive speed and haste of the traditional vibration machine.
[0064] (4) Curing and shaping: The plate pressed in step (3) is sent to a curing furnace, cured at 150° C. for 125 minutes, and then laid flat for shaping for 24 hours to obtain a embryonic plate;
[0065] (5) Thickness determination and polishing: The embryo plate obtained in step (4) is sent to a polishing machine for thickness determination, and then fine polishing is performed using grinding blocks of 26 mesh, 60 mesh, 100 mesh, 300 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1800 mesh, 3000 mesh, and 6000 mesh to obtain a semi-finished artificial stone plate of thermal transfer;
[0066] (6) Lay the semi-finished artificial stone plate obtained in step (5) flat, clean it and keep the surface flat, and place the plate on an insulating support plate through a conveyor line using a suction cup, and preheat it to a specified temperature of 125° C. Then place a transfer paper printed with a high-definition stone pattern, cover it with a high-temperature heat-conducting cloth, and send it to a transfer machine. The heating method of thermal transfer is a six-sided plywood plate type. Heat conduction is achieved through a heat-conducting oil pipe pre-buried in the steel plate. The six-sided plywood oil tank is set to a heat transfer temperature of 210° C. After all six plywoods are in contact with the six sides of the semi-finished artificial stone plate, the heating transfer time is maintained for 30 minutes, so that the pattern on the drawing is thermally sublimated, and the color is transferred and fused to the quartz plate to obtain a plate after thermal transfer;
[0067] (7) The plate after thermal transfer in step (6) is transported from the transfer machine to a clamping plate type insulation furnace for four-stage cooling, wherein the four-stage cooling is firstly kept at 180°C for 30 minutes, then kept at 140°C for 30 minutes, kept at 110°C for 60 minutes, and kept at 70°C for 60 minutes; after the temperature is reduced to 40°C, it is sent to the wire rack and cooled to room temperature, and then a robot is used to separate the cooled artificial stone plate from the support plate to obtain the thermally transferred artificial stone plate.
[0068] Example 3
[0069] A heat transfer artificial stone plate comprises, by weight, 16.6 parts of vinyl unsaturated resin, 55.8 parts of 325-mesh corundum powder, 30.2 parts of 600-mesh quartz powder, 0.20 parts of tert-butyl peroxybenzoate, 0.23 parts of γ-methacryloxypropyltrimethoxysilane, 3.3 parts of 1000-mesh bentonite powder, 0.7 parts of lithium stearate heat stabilizer, 0.3 parts of composite color powder A (the mass ratio of titanium dioxide, iron red powder, iron yellow powder and iron black powder is 5:2:2:1) and 1.5 parts of composite color paste B (the mass ratio of titanium white paste, iron yellow paste, carbon black paste and scarlet paste is 8:3:1:2).
[0070] A method for preparing a thermal transfer artificial stone plate comprises the following steps:
[0071] (1) Stirring: Add vinyl unsaturated resin, tert-butyl peroxybenzoate curing agent, γ-methacryloxypropyl trimethoxysilane coupling agent, composite color paste, and heat stabilizer into a resin stirring barrel and stir evenly, then pour into a stirrer containing pre-mixed corundum powder, quartz powder, and bentonite powder, rotate forward at a low frequency of 10 Hz for 2 minutes, reverse at a low frequency of 10 Hz for 2 minutes, rotate forward at a high frequency of 50 Hz for 3 minutes, reverse at a high frequency of 50 Hz for 3 minutes, and stir and mix for 10 minutes to obtain a mixture;
[0072] (2) Powder spraying: pour the mixed material obtained in step (1) into the mold pad, flatten it, spray the composite color powder, and slightly stir the material layer to obtain a pre-pressed material;
[0073] (3) Vacuum pressing: The mold pad is fed into the press with the pre-pressed material sprayed with powder in step (2), and vacuumed. The material is vibrated at high frequencies in 8 frequency bands: 8 Hz for 20 seconds, 15 Hz for 20 seconds, 20 Hz for 40 seconds, 30 Hz for 30 seconds, 35 Hz for 30 seconds, 40 Hz for 30 seconds, 45 Hz for 60 seconds, and 50 Hz for 30 seconds. The phased and gradual vibration can effectively overcome the vibration problem caused by the excessive speed and haste of the traditional vibration machine.
[0074] (4) Curing and shaping: The plate pressed in step (3) is sent to a curing furnace, cured at 145° C. for 120 minutes, and then laid flat for shaping for 24 hours to obtain a embryonic plate;
[0075] (5) Thickness determination and polishing: The embryo plate obtained in step (4) is sent to a polishing machine for thickness determination, and then fine polishing is performed using grinding blocks of 26 mesh, 60 mesh, 100 mesh, 300 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1800 mesh, 3000 mesh, and 6000 mesh to obtain a semi-finished artificial stone plate of thermal transfer;
[0076] (6) Lay the semi-finished artificial stone plate obtained in step (5) flat and clean it to keep the surface flat. Place the plate on the heat-insulating support plate through the conveyor line with a suction cup and preheat it to a specified temperature of 135° C. Then place the transfer paper printed with a high-definition stone pattern, cover it with a high-temperature heat-conducting cloth, and send it to the transfer machine. The heating method of thermal transfer is a six-sided plywood plate. Heat conduction is achieved through a heat-conducting oil pipe pre-buried in the steel plate. The six-sided plywood oil tank is set to a heat transfer temperature of 210° C. When all six plywoods are in contact with the six sides of the semi-finished artificial stone plate, the heating transfer time is maintained for 30 minutes to allow the pattern on the drawing to be thermally sublimated and the color to be transferred and fused to the quartz plate to obtain a plate after thermal transfer;
[0077] (7) The plate after thermal transfer in step (6) is transported from the transfer machine to a clamping plate type insulation furnace for four-stage cooling, wherein the four-stage cooling is firstly kept at 180°C for 30 minutes, then kept at 140°C for 30 minutes, kept at 110°C for 60 minutes, and kept at 70°C for 60 minutes; after the temperature is reduced to 40°C, it is sent to the wire rack and cooled to room temperature, and then a robot is used to separate the cooled artificial stone plate from the support plate to obtain the thermally transferred artificial stone plate.
[0078] Comparative Example 1
[0079] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses an equal amount of glass powder with the same mesh size to replace the corundum powder in Example 1, and the rest is the same as Example 1.
[0080] Comparative Example 2
[0081] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses an equal amount of calcium carbonate powder of the same mesh size to replace the quartz powder in Example 1, and the rest is the same as Example 1.
[0082] Comparative Example 3
[0083] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses an equal amount of 60-mesh corundum powder to replace the 325-mesh corundum powder in Example 1, and the rest is the same as Example 1.
[0084] Comparative Example 4
[0085] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 uses an equal amount of 400-mesh quartz powder to replace the 600-mesh quartz powder in Example 1, and the rest is the same as Example 1.
[0086] Comparative Example 5
[0087] The only difference between Comparative Example 5 and Example 1 is that Comparative Example 5 uses three-stage cooling (keeping at 180°C for 30 minutes, then keeping at 140°C for 30 minutes, and keeping at 110°C for 60 minutes) to replace the four-stage cooling of Example 1, and the rest is the same as Example 1.
[0088] Comparative Example 6
[0089] The difference between Comparative Example 6 and Example 1 is that Comparative Example 6 uses upper and lower double-sided heating to replace the six-sided heating of Example 1, and the rest is the same as Example 1.
[0090] Performance Testing
[0091] The performance tests were conducted on the artificial stone panels of Examples 1-3 and Comparative Examples 1-6. The test items and test methods are as follows:
[0092] Appearance, clarity of image after transfer: visual;
[0093] Flexural strength, Mohs hardness, abrasion resistance, falling ball impact strength, diagonal center deformation of the plate, average depth of transfer layer: measured in accordance with JC / T 908-2013;
[0094] The test results of the properties of the artificial stone panels of Examples 1-3 and Comparative Examples 1-6 are shown in Table 1.
[0095] Table 1: Test results of artificial stone slab performance of Examples 1-3 and Comparative Examples 1-6
[0096]
[0097]
[0098] As can be seen from Table 1, the artificial stone board prepared by the present invention has good toughness and wear resistance, and is flat, has a clear pattern, a high penetration depth of the transfer layer, a strong three-dimensional sense, and will not crack or deform during processing and cutting. It is a new type of thermal transfer artificial stone product with great aesthetic value and market prospects.
[0099] Comparative Example 1 uses an equal amount of glass powder to replace corundum powder, so that the flexural strength, Mohs hardness, wear resistance, drop ball impact strength, plate diagonal center deformation, image clarity after transfer, and average depth of the transfer layer of Comparative Example 1 are significantly worse than those of Example 1, and the performance is significantly reduced. Comparative Example 2 uses an equal amount of calcium carbonate powder to replace quartz powder, so that the flexural strength, Mohs hardness, wear resistance, drop ball impact strength, plate diagonal center deformation, image clarity after transfer, and average depth of the transfer layer of Comparative Example 2 are significantly worse than those of Example 1, and the performance is poor. Comparative Examples 1 and 2 illustrate that the present invention uses a combination of specific types of corundum powder and quartz powder to obtain an artificial stone product with good toughness, wear resistance, strong texture, and not easy to deform.
[0100] Comparative Example 3 uses an equal amount of 60-mesh corundum powder to replace the 325-mesh corundum powder of Example 1, and Comparative Example 4 uses an equal amount of 400-mesh quartz powder to replace the 600-mesh quartz powder of Example 1, so that the flexural strength, drop ball impact strength, plate diagonal center deformation, and transfer layer average depth of Comparative Example 3 and Comparative Example 4 are significantly worse than those of Example 1, and the surface clarity and texture are poor. This is because the coarse particles of corundum powder and quartz powder with too large mesh cannot be transferred during transfer, while the gap between fine particles is small, which is more conducive to the clarity of the image after transfer. The present invention uses a compound of corundum powder and quartz powder with a specific mesh number, so that the artificial stone board has better effects in hardness, toughness, texture and clarity of the plate after transfer.
[0101] Comparative Example 5 uses three-stage cooling to replace the four-stage cooling of Example 1, so that the flexural strength, falling ball impact strength, deformation, and average depth of the transfer layer of Comparative Example 5 are significantly worse than those of Example 1, indicating that multi-stage thermal insulation and gradual cooling can avoid the problem of the internal stress generated by the board being not completely released due to excessive cooling, thereby avoiding deformation and cracking during later cutting, and can increase the average depth of the transfer layer. Comparative Example 6 uses upper and lower double-sided heating to replace the six-sided heating of Example 1, so that the falling ball impact strength, deformation, image clarity after transfer, and average depth of the transfer layer are significantly worse than those of Example 1. It shows that the thermal transfer method of six-sided heating combined with the four-stage thermal insulation and step-by-step cooling method can make the artificial stone board straight, the pattern clear, the transfer layer penetration depth high, the three-dimensional sense strong, and the processing and cutting will not crack or deform.
[0102] In summary, the present invention combines corundum powder and quartz powder of specific mesh size, and adopts a six-sided pressurized heating transfer method combined with a multi-level insulation and gradual cooling method during thermal transfer, so that the transfer effect is clearer, the transfer depth is better, and the board surface is flat and not easy to deform.
[0103] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An artificial stone plate, characterized in that: Including resin, corundum powder, quartz powder, filler, curing agent, coupling agent; The particle size of the corundum powder is 70-450 mesh; the particle size of the quartz powder is 500-950 mesh.
2. The artificial stone plate according to claim 1, characterized in that: The resin includes at least one of an unsaturated resin and an epoxy resin; and / or the curing agent includes at least one of tert-butyl peroxide 2-ethylhexanoate, methyl ethyl ketone peroxide, tert-butyl perbenzoate, ethylenediamine, and diethylenetriamine; and / or the coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropyltriethoxysilane; and / or the filler includes bentonite.
3. The artificial stone plate according to claim 1, characterized in that: In terms of weight, the artificial stone plate comprises 11-24 parts of resin, 36-70 parts of corundum powder, 20-42 parts of quartz powder, 1.8-8.5 parts of filler, 0.1-1.3 parts of curing agent, and 0.1-1.6 parts of coupling agent.
4. The artificial stone plate according to any one of claims 1 to 3, characterized in that: The artificial stone plate further comprises at least one of a heat stabilizer, a color paste and a color powder.
5. The artificial stone plate according to claim 4, characterized in that: The artificial stone plate also includes a heat stabilizer, a color paste and a color powder; and by weight, the artificial stone plate includes 11-24 parts of resin, 36-70 parts of corundum powder, 20-42 parts of quartz powder, 1.8-8.5 parts of filler, 0.1-1.3 parts of curing agent, 0.1-1.6 parts of coupling agent, 0.3-2.2 parts of heat stabilizer, greater than 0 parts and less than or equal to 0.60 parts of color powder, and greater than 0 parts and less than or equal to 2.4 parts of color paste.
6. The artificial stone plate according to claim 5, characterized in that: The heat stabilizer includes at least one of lithium stearate and zinc stearate; and / or, the color powder includes at least one of titanium dioxide, iron red powder, iron yellow powder, iron black powder, phthalocyanine blue powder and carbon black powder; and / or, the color paste includes at least one of titanium white paste, iron yellow paste, carbon black paste, scarlet paste and phthalocyanine blue paste; and / or, the particle size of the bentonite is 900-3300 mesh.
7. The method for preparing the artificial stone plate according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) mixing, molding and curing the raw material components to obtain the semi-finished artificial stone slab; (2) preheating, thermally transferring, and multi-stage cooling the semi-finished artificial stone slab obtained in step (1) to obtain the artificial stone slab; The thermal transfer is to heat the artificial stone slab semi-finished product on six sides; The multi-stage cooling includes four-stage cooling.
8. The preparation method according to claim 7, characterized in that: In step (1), the forming is compression forming; and / or the curing temperature is 140-160° C., and the curing time is 110-130 min.
9. The preparation method according to claim 7, characterized in that: In step (2), the preheating temperature is 110-150°C, and the preheating time is 1.8-11 minutes; and / or the thermal transfer temperature is 180-220°C, and the thermal transfer time is 25-35 minutes; and / or the four-stage cooling is sequentially kept at 210-155°C for 25-35 minutes, kept at 150-125°C for 25-35 minutes, kept at 120-85°C for 55-65 minutes, and kept at 80-40°C for 55-65 minutes.
10. Use of the artificial stone board according to any one of claims 1 to 6 in the field of construction.